{2*[20-(5+x):6]-5}:9=3
Răspunsuri la întrebare
Răspuns de
1
{2*[20-(5+x):6]-5}:9=3 2*[20-(5+x):6]-5=27 2*[20-(5+x):6]=32 20-(5+x):6=16 (5+x):6=4 5+x=24
x=19
x=19
Răspuns de
0
2*[20-(5+x):6] - 5 = 27 ( 3*9)
2*[20-(5+x):6]=32
20-(5+x):6=16
20-(5+x)=96
5+x=76
x=71
Sper ca te-am ajutat :** :3
2*[20-(5+x):6]=32
20-(5+x):6=16
20-(5+x)=96
5+x=76
x=71
Sper ca te-am ajutat :** :3
Alte întrebări interesante
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă